Occurrence of osteochondromatosis (multiple cartilaginous exostoses) in a domestic pig (Sus scrofa domesticus) - de Brot, Simone; Grau-Roma, Llorenc; Vidal, E.; Segalés, J. (Sage, 2013)
Osteochondromatosis is a condition in which multiple benign, cartilage-capped tumors arise from the surface of bones formed by endochondral ossification. The current report describes the presence of 4 prominent exophytic masses, measuring between 4 and 13 cm in diameter, arising from the surface of the ribs, and located within the thoracic cavity, in a 2-year-old female domestic pig (Sus scrofa domesticus). Histological studies revealed that masses were well-differentiated, cartilage-capped proliferations with an orderly pattern of endochondral mineralization toward deeper areas. The observed gross and microscopic findings are characteristic of osteochondromatosis.